DETECTION OF ANEMIC SYNDROME IN PRIMARY LEUKEMIA PATIENTS - Narmetova M.U., Ulugova Sh.T., Suleymanova D.N. (Confrencea, 2023)
Premorbid background in patients with leukemia is of great importance for the choice of chemotherapy, prognosis of the course and outcome of the leukemic process. One of the most common factors of premorbid background is anemic syndrome. In the developed countries of Europe, America and Japan, the frequency of WAITING is 5-8%. In this regard, anemia as a premorbid background in our republic is of greater importance than in developed countries. According to the literature, anemic syndrome is often found in patients with leukemia, it is caused by circulatory disorders, severe hypoxia. Anemic syndrome also includes certain specific symptoms that are caused by the pathogenetic features of various forms of anemia